2022
DOI: 10.3389/fphys.2022.912049
|View full text |Cite
|
Sign up to set email alerts
|

An optimized protocol for assessment of sputum macrorheology in health and muco-obstructive lung disease

Abstract: Background: Airway mucus provides important protective functions in health and abnormal viscoelasticity is a hallmark of muco-obstructive lung diseases such as cystic fibrosis (CF). However, previous studies of sputum macrorheology from healthy individuals and patients with CF using different experimental protocols yielded in part discrepant results and data on a systematic assessment across measurement settings and conditions remain limited.Objectives: The aim of this study was to develop an optimized and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…To our knowledge rheological data on human intestinal mucus are absent; therefore, we compared our findings on human ileal mucus from controls (n=11) with macrorheological data on human airway mucus from controls (n=10; Figure 1B ). Some of the airway mucus samples from controls were previously included in a publication 33 . The demographic and basic clinical characteristics of the control group for airway mucus are presented in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge rheological data on human intestinal mucus are absent; therefore, we compared our findings on human ileal mucus from controls (n=11) with macrorheological data on human airway mucus from controls (n=10; Figure 1B ). Some of the airway mucus samples from controls were previously included in a publication 33 . The demographic and basic clinical characteristics of the control group for airway mucus are presented in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…We used the previously described macrorheological protocol for human airway mucus 33 . Details are provided in the Supplementary Information .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the viscoelastic properties of the CF and healthy mucus-like hydrogels developed herein were within the same order of magnitude as the viscoelastic properties of CF and healthy airway mucus that have been analyzed and reported in literature. Recent sources have found that healthy and CF airway mucus have storage moduli within the range of 0.2 Pa to 93 Pa and loss moduli within the range of 0.1 Pa to 19 Pa 6,7 . The hydrogels developed here recapitulate the key differences in viscoelastic properties, mucin concentration, and solids concentration in physiological CF and healthy airway mucus.…”
Section: Discussionmentioning
confidence: 99%
“…Airway mucus acts as a protective barrier for the respiratory system by collecting and clearing harmful pathogens from the airways 1,2 . In cystic fibrosis (CF), mutations of the cystic fibrosis transmembrane conductance regulator (CFTR) gene cause the airway epithelial surface to be dehydrated, leading to increased solids and mucin protein concentrations and altered mucus viscoelasticity [3][4][5][6][7] . These altered airway mucus properties impair mucus clearance mechanisms such as mucociliary and cough mediated clearance [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Sputum rheology was measured with a cone and plate rheometer (Kinexus Pro+, Netzsch GmbH, Selb, Germany) as previously described [23]. The elastic modulus (storage modulus, G') and viscous modulus (loss modulus, G′′) were directly extracted from the linear viscoelastic region of the amplitude sweep.…”
Section: Sputum Rheologymentioning
confidence: 99%